Caracterização dos extratos de folhas de chambá (Justicia Pectoralis jacq) e sua eficiência como antimicrobiano natural sobre bactérias transmitidas por alimentos - Guimarães, Thays Lima Fama (2018)
Some plants are used in folk medicine due to their biological activity attributed to their bioactive compounds. The search of consumers for foods with natural ingredients has been driving research aimed at the use of vegetable extracts as natural antimicrobial, replacing synthetic ones. The objective of this work was to obtain extracts of chambá leaves with antimicrobial property aiming its application in the food industry, using safe solvents (Gras). Three extracts of the leaves of chambá were elaborated, being the aqueous extract (EA) by decoction, hydroalcoholic extract 50:50 (EH 50:50) and hydroalcoholic 70:30 (EH 70:30) (alcohol / water) by maceration, having was carried out: its characterization, evaluation of the antimicrobial activity on the bacteria transmitted by food and encapsulation of the dry extract with better results. In the extracts were carried out the analyzes: cytotoxicity, determination of the total phenolic compounds, coumarin and umbelliferone. The EA was selected to perform the encapsulation. Three formulations were elaborated with maltodextrin (T1), cyclodextrin (T2) and combination of maltodextrin and cyclodextrin 1: 1 (T3), subjected to the lyophilization drying process. The microcapsules were analyzed: hygroscopicity, solubility, zeta potential, particle size, color, encapsulation efficiency and antimicrobial activity. The dried extracts obtained did not present cytotoxic action. Total phenolic compounds range from 13430 to 17657.1 mg AGE / 100g and the antioxidant activity from 238.42 to 765,33 µM TE/g. Bactericidal concentrations of Listeria monocytogenes (18 mg / mL), Staphylococcus aureus (1 mg / mL), Escherichia coli (35 mg / mL) and Salmonella enteritidis (18 mg / mL). The action of the bactericidal concentration of the dry aqueous extract against the bacteria tested was confirmed by the electron microscopy images obtained, where sharp changes in their morphologies were verified. The dry EA of the chambá leaf was selected to carry out the microencapsulation, considering that it presented better antimicrobial activity against the bacteria tested, in addition to higher contents of total phenolic compounds and antioxidant activity. The chambá dry EA encapsulated with maltodextrin had the following minimum inhibitory concentrations: 5 mg / mL, 100 mg / mL, 200 mg / mL, 200 mg / mL, for Staphylococcus aureus, Listeria monocytogenes, Salmonella enteritidis and Escherichia coli, respectively. Hygroscopicity ranged from 2.07 to 4.34%, solubility from 74.69 to 75.8%, zeta potential -14.97 to -16.17 mV, particle size 0.58 to 1.15 µm. The microcapsules presented efficient encapsulation of the total phenolic compounds, with 78 to 90%. The formulation with maltodextrin presented more satisfactory results, because it was encapsulated that presented antimicrobial activity for all bacteria studied. The results suggest that the dry aqueous extract of the chambá leaf may be an alternative to the food industry as a natural antimicrobial instead of synthetic ones.